An examination of the capital structure decisions by companies quoted on the Dar es Salaam Stock Exchange. - Kumalija, Jacob (My University, 2013)
This study was carried out in Tanzania. The study was intended to examine the levels of debt and equity employed by companies quoted on the Dar es Salaam Stock Exchange (OSE) in financing their businesses. The study also aimed at identifying the significant factors that influence the capital structure and further to examine the financial managers' opinions on the factors they perceive important in influencing the capital structure. The study focused on 9 selected non-financial companies quoted on the (OSE). The data was collected for 10 years beginning 2000 to 2009 and was obtained from the companies' financial reports and from questionnaires that were mailed to the (CFOs) of all the 9 companies. The most important theories that have guided this study are pecking order theory, agency cost theory and trade-off theory. By using descriptive analysis, it has been found that companies quoted on the (OSE) are on average moderately levered as they prefer relatively more equity to debt. By using regression analysis, the empirical results show that the significant factors influencing the capital structure of companies quoted on the (OSE) are; industry class, company profitability, company size, non-debt tax shields and growth opportunities. Contrary to the outcome of prior studies in developing countries, this study finds that asset tangibility, earnings volatility and effective tax rate are positively related with capital structure. The results of regression are consistent with the opinions of the CFOs except for assets tangibility, earnings volatility and effective tax rate which are perceived by (CFOs) as important factors while the regression analysis shows them as not influential factors on capital structure by companies quoted on the (OSE)The possible explanation for these differences may be that company officials perceive some of the factors as important while in reality they are not. This study makes several contributions to the body of knowledge as well as providing insights to academicians. The study further reveals that there is no single theory that simultaneously predicts the full set of the reliable factors; this warrants further development of the capital structure theories. Finally, the researcher concludes that capital structure decisions varies from country to country and even from industry to industry and should be dealt as such.
Submitted in Partial Fulfillment of the Requirements for the Degree of Master of Commerce
Keywords: Capital Structure; Companies; Stock Exchange; Dar es Salaam